Samutphāp Traiphūm chabap Krung Sī ʻAyutthayā-chabap Krung Thon Burī (Krom Sinlapāk̨̄on, Krasūang Sưksāthikān, 1999)
Pictorial representation Traibhumi, Buddhist cosmology, Phra Nakhon Si Ayutthaya-Thon Buri period.